Analysis of the Factors That Influence Audit Quality at Public Accounting Firms in Surabaya - Mardini, Nindy; Yanthi, Merlyana Dwinda (International Economic Conference of Business and Accounting, 2024)
The number of cases of fraud in financial reporting, such as several examples of cases in Indonesia, indicates that several Public Accounting Firms have low audit quality. Good audit quality is produced by professional auditors in carrying out their work. The independence and content that exists within the auditor is closely related to ethics. This study aims to determine the effect of Competence, Independence, Audit Fee, Auditor Motivation and Auditor Ethics on Audit Quality in Public Accounting Firms in Surabaya. The method used in this research is a quantitative method. Determination of the research sample is by purposive sampling. Data was taken by distributing questionnaires to 13 Public Accounting Firms in Surabaya. 100 questionnaires were distributed and 83 questionnaires were returned. Data measurement was measured using a Likert scale which was then processed using SPSS version 25 software. The results of the t test show the significance of the variables that affect audit quality, including Auditor Independence and Ethics. Meanwhile, the competence, audit fee, and auditor motivation variables have no effect on audit quality.